Nomadismos entre arte e clínica - Andrade, Sabrina Batista (2018)
This research focus on the investigative experimentation of the clinic and performative action as both may be substantiated in self displacement in face of occurring events. It aim a conversation with the produced sense of neoliberal ethos in the current moment which we live in, keeping alert on the risks of collapse that these senses might suffer due to the occurrence of desires being captured and solidified, giving way to habitual and untraceable microfascism. It proposes a clinic that disorganizes this micro-fascism by means of creating and opening a space for liberation and transfer of desires to events that account for new perceptions of reality while creating other forms of presence in the world. By introducing performance to clinic and life, its spaces and behaviors, it may produce alternatives to numbness and normopathy experienced in our bodies